Pre-/in-service teachers’ creativities: behind the creation of multimodal digital storybooks - Tarwiyah, Siti; Dewi, Nuna Mustika; Suja'i, Suja'i (EduLite: Journal of English Education, Literature and Culture, 2024)
The creation of digital storybooks partly represents teachers’ creativity. This study aimed at exploring the pre-/in-service teachers’ creativity in writing multimodal digital storybooks. The data sources of this study were 8 books written collaboratively by 6 teachers and 13 pre-service teachers after involving in a-six-months mentoring program. The data were collected through documentation, then analyzed using content analysis convention of Krippendorff (2013). The study revealed that aspects of creativity were found in the pre-/in-service teachers’ multimodal digital storybooks.  The creativity was presented through integrating reflection sheet, portfolio assessment, using authentic materials, online worksheet, and online quizzes besides the accommodation of new ideas, the use of graphs/diagrams, tables, images, and videos, besides text, the verbal and visual attractiveness, the use of motivational and inspirational sentences. This study suggests that writing multimodal digital storybooks may influence teachers’ pedagogical and content knowledge as well as teachers’ identity.